Robson’s ten group classification: a tool for predicting cesarean section rates - Tiwari, Meghna; Singh, Sanghmitra; Kushwah, Beenu Singh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Increasing cesarean section delivery rates in India and world is a serious maternal health concern. It is important to understand the trends, reasons behind this change and to find ways to achieve optimum cesaerean section (CS) rates. As per the latest data national family health survey 2019-21 (NFHS 5), CS rates at population level in India seems to be 22% while WHO recommends 10-15% threshold. So, we aim to analyze trend of CS and evaluate it according to Robson’s 10 group classification at tertiary care hospital in Rewa, Madhya Pradesh, India. Methods: A cross sectional study was conducted at department of obstetrics and gynecology, Shyam Shah medical college Rewa for 3 years from May 2019 to April 2022 on all deliveries occurring on or after 28 weeks of gestation by cesarean section. Results: Total of 26552 deliveries over 3 years period were analyzed, of these 7484 were CSs (28.18%). Overall C section rate increased from 18.97% in 2019 to 39.95% in 2022. Major contributors to this increase were Robson’s group 5-32.58%, Robson’s group 1-29.45% and Robson’s group 2-12.22%. Conclusions: Robson’s group 1, 2 and 5 were major contributors to overall increased cesarean section rates. Fetal compromise, meconium aspiration risk, obstructed labor and cesarean scar tenderness were underlying indications for most of the cesarean sections done. Efforts should be made to implement standard protocol to reduce primary cesarean section rates.